EFFICIENCY OF SDGS IMPLEMENTATION IN VILLAGE SUSTAINABLE DEVELOPMENT TO REDUCE INCOME DISTRIBUTION INEQUALITY - Putri, Amila Zamzabila; Choiri, Miftakhul (Jurnal Ekonomi dan Bisnis Airlangga, 2024)
Introduction: Village development in Indonesia aims to improve the welfare of the community, especially in terms of income equality. To achieve this goal, people-centered sustainable development is needed. Sustainable development is an effort to improve the quality of life while still trying not to exceed the ecosystem that supports life. Sustainable development in villages can be implemented through the Village SDGs. The Village SDGs include 17 goals that are interconnected with each other. Each goal has specific targets in addressing pressing social, economic, and environmental issues and creating a more just and sustainable future together. The purpose of this study is to determine whether people-centered sustainable development is effective in reducing income distribution inequality and to explain how it affects income distribution inequality. Methods: Using DEA analysis and panel data regression, the research object is 33 provinces in Indonesia. Results: The results show that education and income have a significant negative effect on income inequality. Furthermore, health has a significant positive effect on income distribution inequality. Conclusion and suggestion: Equal access to education, health, and equal income, will be effective in reducing the level of inequality in the community.